Ascorbic acid-loaded nanomaterials, methods for preparing the same, and uses thereof

CN122973648APending Publication Date: 2026-10-27HUIZHOU CENT PEOPLES HOSPITAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411406282.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

[0028]与现有技术相比,本发明的有益效果是;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122973648A_ABST
    Figure CN122973648A_ABST
Patent Text Reader

Abstract

The present application aims at the clinical treatment demand of infection, and discloses a magnesium-iron layered double hydroxide nano adjuvant loaded with ascorbic acid, which has the functions of sterilization and bone immune regulation. The method is to directly synthesize magnesium-iron layered double hydroxide by using hydrothermal one-pot method, and the interlayer of the magnesium-iron layered double hydroxide is loaded with ascorbic acid molecules. The nano adjuvant prepared by the present application has good cell compatibility, and can generate hydroxyl radicals in acid and oxygen, so as to kill the surrounding bacteria. In addition, the magnesium ions, iron ions and ascorbic acid molecules released by the decomposition of the nano adjuvant can induce the polarization of immune cells to the direction of anti-inflammatory and pro-repair, and accelerate the osteogenic differentiation of stem cells, so as to play the role of accelerating bone repair. The present application can be widely applied to the treatment of bone infection or other bacterial related diseases.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of medical nanoparticle technology, and in particular to a nanomaterial loaded with ascorbic acid, its preparation method, and its application. Background Technology

[0002] According to the World Health Organization (WHO), millions of people die globally each year from bacterial infections. Hospital-acquired infections account for a significant proportion of these deaths. An analysis of US hospital infection data suggests that over 75,000 patients die from hospital-acquired infections annually, and this number is likely even higher in developing countries. Antibiotics are the primary means of clinical treatment and infection prevention. However, with the widespread and inappropriate use of antibiotics, bacterial resistance is increasing, rendering previously effective antibiotics ineffective against certain bacteria, limiting treatment options, and increasing the difficulty and risks of treatment.

[0003] Nanotechnology possesses unique advantages, including a large specific surface area and special physicochemical properties, making it suitable for preparing nanomaterials with antibacterial activity. However, currently developed antibacterial nanoadjuvants are mainly based on external field response or elements such as zinc, silver, copper, and sulfur. The former cannot respond to the bacterial infection microenvironment, even if it effectively kills bacteria; the latter may also have significant toxicity to cells, raising concerns about biosafety. On the other hand, for bone infection problems, the prepared nanoadjuvants need to have a certain ability to regulate the immune response at the injury site and stem cell differentiation behavior, thereby accelerating bone repair. Therefore, it is necessary to design safe and effective nanoadjuvants that can actively respond to the bacterial microenvironment, and at the same time, these nanoadjuvants can also regulate bone immunity to promote bone repair. Summary of the Invention

[0004] The purpose of this invention is to address the shortcomings of existing technologies by proposing a nanomaterial loaded with ascorbic acid, its preparation method, and its application. This invention proposes constructing a magnesium-iron layered double hydroxide nanoadjuvant with ascorbic acid loaded in the interlayer. Ascorbic acid, magnesium ions, and iron ions are all substances with excellent biocompatibility. Iron ions can undergo a pro-oxidative reaction with ascorbic acid under acidic and aerobic conditions to generate hydroxyl radicals, thereby killing bacteria. Simultaneously, these three substances can also regulate the immune microenvironment and stem cell behavior, accelerating bone repair.

[0005] To achieve the above objectives, a nanomaterial loaded with ascorbic acid, with the chemical formula Mg... 10 Fe 3.8 (OH) 25.89 (C6H7O6) 4.24 The Fe atoms comprise 33.3% Fe. 2+ With 66.7% Fe 3+ .

[0006] A method for preparing ascorbic acid-loaded nanomaterials includes the following steps:

[0007] Step 1: Prepare magnesium source solution and iron source solution respectively. The magnesium source solution includes at least one of magnesium chloride, magnesium nitrate, and magnesium sulfate. The iron source solution includes at least one of ferric chloride, ferric nitrate, and ferric sulfate.

[0008] Step 2: Mix the magnesium source solution, iron source solution and sodium ascorbate, and add sodium hydroxide solution to adjust the pH of the mixture to alkaline.

[0009] Step 3: Place the mixture in a drying oven and react for at least 2 hours at a temperature above 60°C.

[0010] Step 4: Centrifuge the reacted mixture in a centrifuge, then add deionized water and sonicate to disperse it. Centrifuge again and discard the supernatant.

[0011] Step 5: Place the product obtained in step 4 into a vacuum drying oven for drying.

[0012] Preferably, the magnesium source solution is a magnesium chloride solution, and the iron source solution is a green iron solution. In step one, during solution preparation, a 0.6 mol / L magnesium chloride solution and a 0.2 mol / L ferric chloride solution are prepared using deionized water. The chemical formula is Mg. 2+ +Fe 3+ +C6H7O6 - →Mg 10 Fe 3.8 (OH) 25.89 (C6H7O6) 4.24

[0013] Preferably, the sodium ascorbate solution has a concentration of 176 mg / L, and the molar ratio of the magnesium chloride solution, ferric chloride solution, and sodium ascorbate solution is 30:10:1.

[0014] Preferably, the sodium hydroxide solution in step two is 0.1 mol / L, and the pH value of the mixed solution after adjustment is 9.5.

[0015] Preferably, in step three, the mixture is poured into a polytetrafluoroethylene reactor and lined with a stainless steel outer liner, and reacted in an electric heating drying oven at 80°C for 4 hours.

[0016] Preferably, in step four, the mixture is centrifuged in a 10,000g centrifuge for 10 minutes, the supernatant is removed, deionized water is added, and the mixture is ultrasonically dispersed. Then, it is centrifuged in a 10,000g centrifuge for another 10 minutes, and the supernatant is removed.

[0017] Application of an ascorbic acid-loaded nanomaterial, wherein the ascorbic acid-loaded nanomaterial is used in bone infections or other clinical infections.

[0018] Preferably, the ascorbic acid-loaded nanomaterials are subjected to Mg under acidic and oxygen-containing environments. 10 Fe 3.8 (OH) 25.89 (C6H7O6) 4.24 Generates hydroxyl radicals, Me 2+ Fe 2+ Fe 3+ C6H7O6 - The following ascorbic acid ions are C6H7O6 - Use AscH - The chemical formula for substitution and decomposition is:

[0019] In Fe 3+ Under the catalysis of AscH, the reaction occurs. - +O2→Asc· - +HO2·

[0020] Asc· - +Fe 3+ →DHA+Fe 2+

[0021] Asc· - +O2→DHA+O2· -

[0022] Fe 2+ +HO2·+H + →Fe 3+- +H2O2

[0023] Fe 2+ +H₂O₂→Fe 3+ +·OH

[0024] Asc· - The chemical formula is C6H7O6· - Its molecular structure is

[0025] DHA is dehydroascorbic acid, with the chemical formula C6H6O6 and molecular structure [missing information].

[0026]

[0027] Preferably, bacteria are killed by oxidative stress caused by reactive oxygen species (i.e., hydroxyl radicals ·OH). Hydroxyl radicals have a good killing effect on bacteria such as Escherichia coli and Staphylococcus aureus. Magnesium ions and iron ions are bioactive ions that are also abundant in bone. Providing these two ions can directly promote the bone repair process. Magnesium ions are also a common bone immune regulatory ion that can induce macrophages to polarize into the anti-inflammatory M2 type. Then, M2 macrophages secrete tissue repair factors such as IL-4, IL-10, and Arg, which accelerates bone repair from an immune perspective. Magnesium ions can also induce bone marrow stem cells to differentiate into osteogenic cells.

[0028] Compared with the prior art, the beneficial effects of the present invention are:

[0029] The nano-formulation involved in this invention is produced by a one-step hydrothermal process, which is simple and conducive to large-scale production. Secondly, the raw materials used are only magnesium salts, iron salts, and sodium ascorbate; all reagents are conventional, safe, readily available, and inexpensive, making the preparation safe and economical. Finally, the ascorbic acid-loaded magnesium-iron layered double hydroxide prepared by this invention can respond to the acidic microenvironment of bacteria, generating hydroxyl radicals to kill bacteria. It can also regulate the immune response by releasing magnesium ions, iron ions, and ascorbic acid, promoting osteogenic differentiation of bone stem cells, and can be used to treat clinical bacterial infections, especially bone-related infections. Attached Figure Description

[0030] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the accompanying drawings used in the embodiments will be briefly described below.

[0031] Figure 1 Transmission electron microscopy (TEM) images of the ascorbic acid-free magnesium-iron layered double hydroxide (LDH) and the ascorbic acid-loaded magnesium-iron layered double hydroxide (ALDH) of the present invention.

[0032] Figure 2 This is an elemental distribution diagram of the ALDH sample of the present invention;

[0033] Figure 3 The X-ray diffraction (XRD) patterns of the LDH and ALDH samples of this invention are shown.

[0034] Figure 4 The ability of the ALDH sample of this invention to catalyze 3,3',5,5'-tetramethylbenzidine dihydrochloride (TMB) at different pH values;

[0035] Figure 5 The ability of the ALDH sample of this invention to catalyze 3,3',5,5'-tetramethylbenzidine dihydrochloride (TMB) under different atmospheres;

[0036] Figure 6 The antibacterial efficiencies of the LDH and ALDH samples of this invention against Staphylococcus aureus and Escherichia coli are shown.

[0037] Figure 7 The expression of pro-inflammatory M1 and anti-inflammatory M2 genes in RAW 264.7 of this invention after culturing with LDH and ALDH samples for 3 days is shown.

[0038] Figure 8 This invention aims to clear the expression of osteogenic-related genes after C3H10 was cultured with LDH and ALDH samples for 3 and 7 days, respectively. Detailed Implementation

[0039] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments and the accompanying drawings. It should be understood that these descriptions are merely exemplary and not intended to limit the scope of the invention. Furthermore, descriptions of well-known structures and techniques are omitted in the following description to avoid unnecessarily obscuring the concept of the invention.

[0040] Example 1

[0041] First, prepare a 0.6 mol / L magnesium chloride solution and a 0.2 mol / L ferric chloride solution using deionized water. The mass ratio of magnesium chloride solution to sodium chloride solution is 3:1. Mix the two solutions and adjust the pH to 9.5 using 0.1 mol / L sodium hydroxide. Then, quickly pour the mixture into a polytetrafluoroethylene (PTFE) reactor, lined with a stainless steel outer shell, and react in an electrically heated drying oven at 80°C for 4 hours. Centrifuge the obtained nano-adjuvant at 10000g for 10 minutes, discard the supernatant, add deionized water, and ultrasonically disperse. Then centrifuge again at 10000g for 10 minutes, discard the supernatant, and dry in a vacuum drying oven. The resulting sample is labeled LDH.

[0042] like Figure 1 The image shows the transmission electron microscopy (TEM) morphology of the nano-adjuvant obtained through the modification treatment in this embodiment. As can be seen from the image, the LDH sample exhibits a nanosheet-like structure, a typical layered double hydroxide morphology. The minor axis of the sheets is approximately 80 nm, and the major axis is approximately 150 nm. Figure 3 The XRD pattern of the nano-adjuvant obtained by the modification treatment in this embodiment is shown. It can be seen from the figure that there are obvious characteristic peaks of the (003) and (006) crystal planes representing layered double hydroxides at around 12° and 24°.

[0043] Example 2

[0044] First, prepare a 0.6 mol / L magnesium chloride solution, a 0.2 mol / L ferric chloride solution, and a 176 mg / L sodium ascorbate solution using deionized water. Mix these three solutions and adjust the pH to 9.5 using 0.1 mol / L sodium hydroxide. Then, quickly pour the mixture into a polytetrafluoroethylene (PTFE) reactor, lined with a stainless steel outer liner, and react in an electrically heated drying oven at 80°C for 4 hours. Centrifuge the obtained nano-adjuvant at 10000 g for 10 minutes, discard the supernatant, add deionized water, and sonicate. Then centrifuge again at 10000 g for 10 minutes, discard the supernatant, and dry in a vacuum drying oven. The resulting sample is labeled ALDH.

[0045] like Figure 1 The image shows the transmission electron microscopy (TEM) morphology of the nano-adjuvant obtained through the modification treatment in this embodiment. As can be seen from the image, the ALDH sample exhibits a nanosheet-like structure, a typical layered double hydroxide morphology. The minor axis of the sheets is approximately 60 nm, and the major axis is approximately 120 nm. Figure 2 An elemental distribution diagram of the nano-adjuvant obtained through the modification treatment in this embodiment is provided. The diagram shows that the main elemental composition of the ALDH sample is Mg, Fe, O, and C. Figure 3 The XRD pattern of the nano-adjuvant obtained by the modification treatment in this embodiment is shown. It can be seen from the figure that there are obvious characteristic peaks of the (003) and (006) crystal planes representing layered double hydroxides at around 12° and 24°.

[0046] Example 3

[0047] Prepare a 20 mmol / L TMB solution and dilute it 10-fold with 0.9 wt.% NaCl. Then, adjust the pH of the solution to 7.4, 6.5, and 6 with dilute hydrochloric acid, respectively. Add ALDH powder sample to the TMB solutions at different pH values. Incubate in the dark for 30 minutes. Transfer 100 μL of the reaction solution to a 96-well plate and detect the absorbance of the solution in the 450-800 nm range using a Cytation5 multimode reader (BioTek, USA).

[0048] like Figure 4 The graph shows the absorbance values ​​of the ALDH sample solution after catalytic decomposition of TMB at different pH values. As can be seen from the graph, the lower the pH value, the stronger the ALDH powder's ability to catalyze the decomposition of TMB, indicating the generation of more hydroxyl radicals.

[0049] Example 4

[0050] Prepare a 20 mmol / L TMB solution and dilute it 10-fold with 0.9 wt.% NaCl. Then, adjust the pH of the solution to 6 with dilute hydrochloric acid. Incubate the TMB solutions in different atmospheres for 12 hours in the dark. Then, add ALDH powder samples to the TMB solutions in different atmospheres and incubate in the dark for 30 minutes. Transfer 100 μL of the reaction solution to a 96-well plate and measure the absorbance of the solution in the 450-800 nm range using a Cytation 5 multimode reader (BioTek, USA).

[0051] like Figure 5 The graph shows the absorbance values ​​of the ALDH sample solution after catalytic decomposition of TMB under different atmospheres. As can be seen from the graph, the higher the oxygen content, the stronger the ALDH powder's ability to catalyze the decomposition of TMB, indicating the generation of more hydroxyl radicals.

[0052] Example 5

[0053] The antibacterial activity of LDH and ALDH samples was evaluated using Gram-positive Staphylococcus aureus and Gram-negative Escherichia coli. 200 μL of bacteria (1 × 10⁷ CFU / mL) was mixed with 200 μL of nano-adjuvant (400 μL / mL) in a 1 mL EP tube and cultured. After 24 hours of incubation in a bacterial incubator, the culture was shaken thoroughly, and 100 μL was taken and diluted 100-fold. Then, 100 μL of the diluted bacterial solution was transferred to an agar plate and spread evenly using a sterile glass spreader. The agar plate was placed in a bacterial incubator for 18 hours. Finally, the agar plate was photographed.

[0054] The experimental results of this embodiment are as follows: Figure 6 As shown in the figure, the LDH sample without ascorbic acid loading had almost no killing effect on either bacterium. However, the ALDH sample loaded with ascorbic acid showed a significant inhibitory effect on both bacteria.

[0055] Example 6

[0056] The effects of LDH and ALDH samples on immune cells were assessed using RAW264.7 cell culture in vitro and qRT-PCR. The specific methods are as follows:

[0057] 1) Cell culture: 500 μL of cells (5×104 CFU / mL) were mixed with 500 μL of nano-adjuvant (400 μL / mL) and cultured in a 124-well plate.

[0058] 2) RNA extraction: After culturing for 3 days, the culture medium was discarded, cells were lysed with Trizol, and RNA purity was detected using a Nanodrop spectrophotometer.

[0059] 3) Reverse transcription: Reverse transcription was performed using a cDNA first-strand synthesis kit, and the resulting cDNA was stored at -20℃.

[0060] 4) Real-time quantitative PCR: Then, the cDNA was mixed with SYBR Green Mastermix and primers, and the relative gene expression level of the target gene was calculated using the 2-ΔΔct method.

[0061] like Figure 7 This figure shows the expression of M1 (IL-1β, iNOS, and TNF-α) and M2 (IL-4, IL-10, and Arg) genes after co-culturing LDH and ALDH samples with macrophages for 3 days. As can be seen from the figure, compared to the blank control group and the LDH group, the expression of M1 genes (IL-1β and TNF-α) decreased in the ALDH sample group, while the expression of M2 genes (IL-4, IL-10, and Arg) increased.

[0062] Example 7

[0063] The effects of LDH and ALDH samples on immune cells were assessed using in vitro C3H10 cell culture and qRT-PCR. The specific methods are as follows:

[0064] 1) Cell culture: 500 μL of cells (5×104 CFU / mL) were mixed with 500 μL of nano-adjuvant (400 μL / mL) and cultured in a 124-well plate.

[0065] 2) RNA extraction: The culture medium was discarded at 3 days and 7 days of culture, the cells were lysed with Trizol, and the RNA purity was detected by Nanodrop spectrophotometer.

[0066] 3) Reverse transcription: Reverse transcription was performed using a cDNA first-strand synthesis kit, and the resulting cDNA was stored at -20℃.

[0067] 4) Real-time quantitative PCR: Then, the cDNA was mixed with SYBR Green Mastermix and primers, and the relative gene expression level of the target gene was calculated using the 2-ΔΔct method.

[0068] like Figure 8 The figure shows the expression of osteogenic-related genes in LDH and ALDH samples after co-culturing with C3H10 for 3 and 7 days. As can be seen from the figure, compared with the blank control group and the LDH group, at 3 days, the Runx2, ALP, and OPN genes in the ALDH sample group were significantly upregulated; at 7 days, OCN and OPN in the ALDH sample group were also significantly upregulated. At 7 days, there was no significant difference in ALP and Runx2 gene expression between the ALDH and LDH sample groups, but both were significantly higher than those in the blank control group.

[0069] The results of Examples 3-8 above show that the ascorbic acid-loaded magnesium-iron layered double hydroxide can efficiently generate hydroxyl radicals in acidic and aerobic microenvironments, and inhibit the proliferation of Staphylococcus aureus and Escherichia coli. Simultaneously, the ascorbic acid-loaded magnesium-iron layered double hydroxide nanoadjuvant can inhibit M1 polarization of macrophages and promote M2 polarization, exhibiting good immunomodulatory properties. Finally, the ascorbic acid-loaded magnesium-iron layered double hydroxide nanoadjuvant can promote osteogenic differentiation of stem cells. The ascorbic acid-loaded magnesium-iron layered double hydroxide nanoadjuvant prepared in this invention is expected to be widely used in the treatment of bone infections or other bacterial-related diseases.

[0070] It should be understood that the specific embodiments described above are merely illustrative or explanatory of the principles of the invention and do not constitute a limitation thereof. Therefore, any modifications, equivalent substitutions, improvements, etc., made without departing from the spirit and scope of the invention should be included within the protection scope of the invention. Furthermore, the appended claims are intended to cover all variations and modifications falling within the scope and boundaries of the appended claims, or equivalent forms of such scope and boundaries.

Claims

1. A nanomaterial loaded with ascorbic acid, characterized in that, The chemical formula is Mg 10 Fe 3.8 (OH) 25.89 (C6H7O6) 4.24 The Fe atoms comprise 33.3% Fe. 2+ With 66.7% Fe 3+ .

2. The method for preparing ascorbic acid-loaded nanomaterials according to claim 1, characterized in that, Includes the following steps: Step 1: Prepare magnesium source solution and iron source solution respectively. The magnesium source solution includes at least one of magnesium chloride, magnesium nitrate, and magnesium sulfate. The iron source solution includes at least one of ferric chloride, ferric nitrate, and ferric sulfate. Step 2: Mix the magnesium source solution, iron source solution and sodium ascorbate, and add sodium hydroxide solution to adjust the pH of the mixture to alkaline. Step 3: Place the mixture in a drying oven and react for at least 2 hours at a temperature above 60°C. Step 4: Centrifuge the reacted mixture in a centrifuge, then add deionized water and sonicate to disperse it. Centrifuge again and discard the supernatant. Step 5: Place the product obtained in step 4 into a vacuum drying oven for drying.

3. The method for preparing ascorbic acid-loaded nanomaterials according to claim 2, characterized in that, The magnesium source solution is a magnesium chloride solution, and the iron source solution is a green iron solution. In step one, during the solution preparation process, 0.6 mol / L magnesium chloride solution and 0.2 mol / L iron chloride solution are prepared using deionized water.

4. The method for preparing ascorbic acid-loaded nanomaterials according to claim 3, characterized in that, The sodium ascorbate solution has a concentration of 176 mg / L, and the molar ratio of the magnesium chloride solution, ferric chloride solution, and sodium ascorbate solution is 30:10:

1.

5. The method for preparing ascorbic acid-loaded nanomaterials according to claim 1, characterized in that, The sodium hydroxide solution mentioned in step two is 0.1 mol / L, and the pH value of the mixed solution after adjustment is 9.

5.

6. The method for preparing ascorbic acid-loaded nanomaterials according to claim 1, characterized in that, In step three, the mixture is poured into a polytetrafluoroethylene reactor and lined with a stainless steel outer liner. It is then reacted in an electric heating drying oven at 80°C for 4 hours.

7. The method for preparing ascorbic acid-loaded nanomaterials according to claim 1, characterized in that, In step four, the mixture is centrifuged in a 10,000g centrifuge for 10 minutes, the supernatant is removed, deionized water is added, and the mixture is ultrasonically dispersed. Then, it is centrifuged in a 10,000g centrifuge for another 10 minutes and the supernatant is removed.

8. The application of the ascorbic acid-loaded nanomaterial according to claim 1, characterized in that, Application of the nanomaterials loaded with ascorbic acid in bone infections or other clinical infections.

9. The application of the ascorbic acid-loaded nanomaterial according to claim 8, characterized in that, The ascorbic acid-loaded nanomaterials are subjected to Mg in acidic and oxygen-containing environments. 10 Fe 3.8 (OH) 25.89 (C6H7O6) 4.24 Generates hydroxyl radicals, Me 2+ Fe 2+ Fe 3+ C6H7O6 - .

10. The application of the ascorbic acid-loaded nanomaterial according to claim 9, characterized in that, Hydroxyl radicals have a good bactericidal effect on bacteria such as Escherichia coli and Staphylococcus aureus; Me 2+ Fe 2+ Fe 3+ Promotes bone repair process; Me 2+ It can regulate the polarization of macrophages toward anti-inflammatory purposes and induce bone marrow stem cells to differentiate toward osteogenic purposes.